THE BLENDED LEARNING: THE TENTH GRADERS’ PERCEPTION OF FACE-TO-FACE AND ONLINE EFL LESSON AT SMAN 4 TARAKAN - Muliawaty, Wandha; Errie Diru, Achmad; arifin, arifin; Ulfaika, Romlah (English Education Department, 2023)
The objective of this research is to obtain perceptions from the tenth-grade students of SMAN 4 Tarakan which is undergoing blended learning. This study used a quantitative approach with a survey method. The subject of the research was 36 students of X-4 at SMAN 4 Tarakan. The data collected was a closed questioner using Likert scale. The results showed that more students admit that they are more motivated and perform better when taking EFL class that are conducted face-to-face. This is in line with the results of the study which showed that in terms of motivation, students were categorized as very motivated when doing face-to-face learning for the EFL class. In addition, students are also categorized as very good in terms of achievements when participating in EFL class which are conducted face-to-face. So it can be concluded that students prefer and need face-to-face learning more than online learning in English class.